Initial result on electrical impedance tomography - Abdul Rahim, Ruzairi; Liew, Yi Huei; Chan, Kok San; Pang, Jon Fea; Leong, Chai Lean (Penerbit UTM Press, 2003)
Electrical Impedance Tomography (EIT) provides a low-cost measurement instrument for monitoring distributions of electrically conducting materials in pipelines and process vessels. This paper describes the development of an eight electrode EIT hardware system test on an 84mm diameter flow pipe. The measurement of two different water pipe conditions will be compared: water-filled only and water-filled with solid object are presented within the boundary of the measurement.